PENDAMPINGAN BIMBINGAN BELAJAR DI MASA PANDEMI COVID 19 DI TKK NEGERI HARAPAN BANGSA KOELODA - Elisabeth Tantiana Ngura; Dominika Diki Sada; Elisabeth Bule Ati; Elisabeth Mogi; Elfrida Tawa Ito; Maria Fausta Tunga; Maria F. K. Rakas; Maria Fransiska Serliana Nimat; Maria Goreti Liu To; Maria Susanti Azi Tawa; Serliana Ladja Laga; Trista Talun; Yessi H. Bude; Yasinta Owa (Jurnal Abdimas Ilmiah Citra Bakti, 2022)
Covid 19 or also known as novel corona virus is in invectious disease caused by a new corona virus, namely Sars cos-2 which was first reported in Wuhan, China on Desember 31, 2019. Indonesia itself has announcad the exsistence of a special covid 19 in March 2020. One of the government’s efforts in breaking the chain of spread of covid 19 is the implementation of school from home or sachool from home during the pandemic, this makes parents in the Todabelu village. Golewa admitted that it was difficult to accompany her children to study at home, both in explaining the subject matter and in dividing their time with their work. In addition, School From Home also makes children experience difficulty in learning and become easily bored at home. The visible results of this learning mentoring activity are that the principal and teachers of the Harapan Bangsa TKKN Koeloda are very supportive and appreciate the tutoring activities carried out by students for several children at the Harapan Bangsa TKKN. The initial test is carried out orally in the form of introductory questions relating to the material the child has previously studied and about the initial understanding of the material to be studied. The final test is carried out in the form of oral and written tests related to understanding and mastery of the material that has been studied together.